2017
DOI: 10.1016/j.apsusc.2017.07.070
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium clustering process on defective (8,0) SWCNT: Analysis of chemical and physical properties using density functional theory

Abstract: Rhodium clustering process on defective (8,0) SWCNT: Analysis of chemical and physical properties using density functional theory, Applied Surface Sciencehttp://dx. HighlightsRh3 and Rh4 clusters prefer to be adsorbed on oxygenated vacancy. Rh adsorption induces a magnetic moment. Rh atom and Rh2 dimer bonded to the defective SWCNT, show a semiconductor behavior. Rh3 and Rh4 show a metallic behavior. AbstractThe Spin-polarized density functional theory is used to study the effect of a single vacancy in a (8,0)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…[22] found that Ti atoms prefer to form clusters on the C 60 surface. Similar results are reported on SWCNT with Rh [18,19]. On the other hand, a theoretical study reports that doping carbon fullerenes with alkali atoms (Li, Na and K) improves the molecular hydrogen adsorption capacity of them [23].…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…[22] found that Ti atoms prefer to form clusters on the C 60 surface. Similar results are reported on SWCNT with Rh [18,19]. On the other hand, a theoretical study reports that doping carbon fullerenes with alkali atoms (Li, Na and K) improves the molecular hydrogen adsorption capacity of them [23].…”
Section: Introductionsupporting
confidence: 83%
“…This supercell size ensures no interaction among periodic images. For simulate the vacancy one C atom is removed, a detailed description of this defective nanotube was reported on our previous work [18].…”
Section: Computational Modelmentioning
confidence: 99%
“…Speaking of the performance of Ag 3 doping on the HfSe 2 monolayer, three doped sites were taken into account. They are named T se1 (a tripod site right upside the lower-layer Se atoms), T se2 (right upside the upper-layer Se atoms), and T Hf (a tripod site right upside the mid-layer Hf atoms) ( Ambrusi et al, 2017 ; Ju et al, 2017 ; Mi et al, 2021 ). As far as the most stable doped configuration, the lower the binding energy ( E b ), the more stable is the structure.…”
Section: Resultsmentioning
confidence: 99%
“…These structural findings are in agreement with literature. 65,66 After the O-O bond breaking and the C-O-Fe bond formation, a larger excess of electrons on the O (label as O 1 in Table 3) is found respect to that corresponding to the oxygen in the O-Fe bond (label as O 2 in Table 3). The iron atom state remains unchanged (Bader charge value E+1|e|) after dissociation.…”
Section: Oxygen Adsorption and Dissociation On Fe@cnt Materialsmentioning
confidence: 99%